The influence of respiratory muscle fatigue on inactive limb blood flow during cycling exercise - Smith, Joshua R. (Kansas State University, 2013)
An increased work of breathing during heavy whole body exercise can lead to respiratory muscle fatigue (RMF) and decreased leg blood flow. Heavy exercise also increases inactive limb and cutaneous blood flow. It is not known, however, how RMF affects inactive limb and cutaneous blood flow. Therefore, we tested the hypothesis that RMF during heavy exercise would reduce: 1) inactive limb blood flow, 2) inactive limb vascular conductance, and 3) inactive limb cutaneous blood flow. Twelve healthy men (23 ± 2 yrs) completed baseline pulmonary function tests followed by an incremental cycle test to VO[subscript]2[subscript]max. Subjects then cycled at both 70% and 85%VO2max (randomized) for 20 minutes. Subjects performed a second 85%VO[subscript]2[subscript]max test ingesting N-acetylcysteine (NAC) (1800mg), which has been reported to reduce RMF, 45 minutes prior the test. Maximum inspiratory pressures (P[subscript]Imax) were measured prior to and immediately following each exercise trial to determine RMF. During exercise, brachial artery blood flow (BABF) was measured via Doppler ultrasound and arm cutaneous blood flow was assessed by laser-Doppler flowmetry. Cutaneous vascular conductance (CVC) was calculated as flux/mean arterial pressure and scaled as % maximal CVC (sites heated to 46[degrees]C). Mean arterial pressure (MAP) was measured manually. Significant RMF occurred with 85%VO[subscript]2[subscript]max (12.8 ± 9.8%), but not with 70%VO[subscript]2[subscript]max (p>0.05). BABF significantly increased from baseline to end exercise in both conditions and was significantly lower (~18%) following the 85%VO[subscript]2[subscript]max test. The amount of RMF at 85%VO[subscript]2[subscript]max was inversely related to the change in BABF (r= -0.66, p<0.05). BA vascular conductance was significantly higher at end exercise at 70%VO[subscript]2[subscript]max compared to 85%VO[subscript]2[subscript]max (2.60 ± 0.73 vs. 2.00 ± 0.42 mLmin[superscript]-1mmHg[superscript]-1, resp.). The amount of RMF at 85%VO[subscript]2[subscript]max was inversely related to BA vascular conductance at end exercise (r= -0.80, p<0.05). Cutaneous vascular conductance was not different (p>0.05) between trials. With NAC, RMF was reduced and BABF was consequently significantly higher (~30%) compared to 85%VO[subscript]2[subscript]max. These data suggest that RMF during heavy whole body exercise decreases inactive arm blood flow and vascular conductance, but not cutaneous blood flow.
Keywords: Respiratory; Kinesiology (0575)